THE INFLUENCE OF PRODUCT ASSORTMENT AND WORD OF MOUTH ON PURCHASE DECISION MEDIATED BY BRAND AWARENESS AMONG BOGAJAYA RETAIL OUTLET CONSUMERS AT JUANDA INTERNATIONAL AIRPORT, EAST JAVA - Christian Henry Hantoro; Rifki Hanif; Teguh Widodo (Universitas KH. Abdul Chalim Mojokerto, 2026)
This explanatory research aims to comprehensively investigate the causal dynamics between product variety (Product Assortment), social referrals (Word of Mouth), and consumer purchasing execution (Purchase Decision), by positioning Brand Awareness as an intervening variable. The study context is focused on the consumers of the Bogajaya Retail Outlet operating within the travel retail environment of Juanda International Airport, a commercial ecosystem heavily characterized by high passenger mobility and severe time-pressure. A quantitative research design was applied, utilizing survey questionnaires distributed to 92 respondents selected through a purposive sampling technique. Data processing and structural evaluations were executed using the Partial Least Squares - Structural Equation Modeling (PLS-SEM) approach via SmartPLS 3.0 software. The structural model evaluation revealed several crucial empirical findings. The Product Assortment dimension failed to exert any significant direct effect on either Brand Awareness or Purchase Decision. In stark contrast, Word of Mouth consistently generated a positive and significant impact on both brand cognition and transaction certainty. Furthermore, Brand Awareness held the most dominant leverage in triggering the execution of Purchase Decisions. In the mediation analysis, Brand Awareness was proven to act as an indirect-only mediation bridging product completeness with purchase decisions, while simultaneously serving as a complementary mediation to amplify the influence of Word of Mouth toward sales conversion. This research culminates in the managerial conclusion that within a fast-paced travel retail landscape, the physical variety of store displays acts merely as a passive attribute that strictly requires a cognitive catalyst (Brand Awareness) to generate economic value. Additionally, the flow of organic reviews holds an absolute role as a